Is Pterygium Morphology Related to Loss of Corneal Endothelial Cells? A Cross-Sectional Study - Zaidi SBH (Dove Medical Press, 2021)
Syed Bilal Hassan Zaidi,1 Wajid Ali Khan2 1Department of Ophthalmology, Mater Misericordiae University Hospital, Dublin, Ireland; 2Pakistan Institute of Ophthalmology (PIO), Department of Cornea and Refractive Surgery, Al-Shifa Trust Eye Hospital, Rawalpindi, PakistanCorrespondence: Syed Bilal Hassan ZaidiDepartment of Ophthalmology, Mater Misericordiae University Hospital, Dublin, IrelandTel +353899568074Email syedbilalhassanzaidi@gmail.comPurpose: To determine the difference in mean corneal endothelial cell density (CECD) between the healthy and diseased eyes of the patients with unilateral pterygium with different morphology patterns by using a non-contact specular microscope (SP2000: Topcon Corporation, Japan) and to find out any relationship between severity of pterygium and daily sunlight exposure with the CECD loss.Methods: A descriptive cross-sectional prospective study was carried out at Al-Shifa Trust Eye Hospital (ASTEH), Rawalpindi, Pakistan from 21st January 2019 to 22nd January 2020. Two hundred eyes (n= 100 patients) of age range18 -68 years with unilateral pterygium were selected. Necessary demographic data and essential variables like age, smoking status, occupation, and daily direct sunlight exposure were determined. The severity of pterygium (grading) based on its morphology was determined by slit-lamp examination. CECD of each patient was carried out using a non-contact Specular Microscope. The healthy eye (without pterygium) of a patient was considered as control.Results: The age range in this study was 18– 68 years, with a mean age of 43.80 ± 24.37 years with a male to female ratio of 1.6:1 (62.00% males vs 38% females). Out of six occupations, the most common occupation was labour/construction work (n=31) followed by farming (n=27). The study reported a mean corneal endothelial cell density (CECD) of 2411.61± 143.64 vs 2751.41 ± 123.674 cells/mm2 in diseased and normal eyes, respectively (p-value = 0.0001). CECD was lower in grade 3 pterygium compared to less severe pterygium { grade 3 (Fleshy) =2261 cells/mm2 vs grade 2 (Intermediate)= 2413 cells/mm2 vs grade 1 (Atrophic)=2459 cells/mm2} although this difference between the groups was not found to be significant (p=0.065). No significant association between sunlight exposure and CECD loss was observed (p=0.065).Conclusion: This study concluded that the mean corneal endothelial cell density in patients with unilateral pterygium using a non-contact specular microscope were 2411.61± 143.64 cells/mm2.Keywords: pterygium, corneal endothelial cell density, specular microscope